(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
The primary focus of this study was to determine the effect of portfolio assessment on final examination scores of EFL students’ writing skill. To determine the impact of portfolio-based writing assessment 40 university students who enrolled in composition course were initially selected and divided randomly into two experimental and control groups. A quasi-experimental research design was adopted in this study. In order to appraise the homogeneity of the experimental and control groups Comprehensive English Language Test (CELT) was employed at the beginning of the study. The pre-test was applied to both the experimental group and control group. Later in the study, a post-test of dependent variables was implemented for both groups. Data analysis was carried out by SPSS 16 statistical computer program .The statistical techniques being applied were the Levene statistic of One-Way ANOVA and the Paired-sample T-test. The results of the study revealed that that students whose work was evaluated by a portfolio system (portfolio-based assessment) had improved in their writing and gained higher scores in final examination when compared to those students whose work was evaluated by the more traditional evaluation system (non-portfolio-based assessment).The findings of the present study highlighted the fact that portfolio assessment could be used as a complementary alternative along with traditional assessment to shed new light on the process of writing.